Kontestasi Konsep Persetujuan : Rekonstruksi Komparatif Perkosaan dalam Perkawinan Berdasarkan Hukum Pidana Indonesia dan Hukum Islam - Mimin Mintarsih; Lukman Mahdami; Ahyar Ari Gayo; Ratna Galuh Manika Trisista (Jurnal Penelitian Hukum De Jure, 2025)
Marital rape is an issue that generates contestation over the concept of consent within marital relations. In Indonesian criminal law, rape is generally understood as a crime that occurs outside marriage, whereas in Islamic law, sexual relations are viewed as part of mutual rights and obligations between husband and wife. This difference in paradigm creates conceptual tension regarding the boundaries between duty, rights, and consent within marriage. This study arises from a literature gap, as previous research has not comprehensively examined the interrelation between the concept of consent in Indonesian criminal law and the concept of riḍā in Islamic law. Existing studies tend to separate the two frameworks without exploring their potential normative and moral intersections as a foundation for legal development. The study aims to comparatively reconstruct the meaning of consent in the context of sexual coercion within marriage according to Indonesian criminal law and Islamic law. The research employs a normative juridical method with statutory, conceptual, and comparative approaches, analyzing the Old and New Criminal Codes, the Law on Sexual Violence Crimes, the Law on the Elimination of Domestic Violence, as well as fiqh principles and maqāṣid al-syarī‘ah. The findings reveal that both legal systems reject sexual coercion, yet differ in their normative foundations, moral objectives, and forms of legal recognition. A comparative reconstruction is therefore required through the reinterpretation of the concept of riḍā in Islamic law and the affirmation of equality principles within national criminal law, in order to strengthen the recognition of consent in marital relations. These findings demonstrate a substantive convergence between positive law and Islamic principles in upholding justice, consent, and individual dignity, while opening pathways for the development of a more responsive legal framework regarding marital rape in Indonesia.